THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON ORGANIZATIONAL COMMITMENT OF LIBRARY PERSONNEL IN PUBLIC SENIOR HIGH SCHOOLS IN JAMBI PROVINCE - Athiatul Haqqi; Mukhtar Latif; Rusmini; Asrulla (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the influence of leadership style, organizational culture, and work motivation on organizational commitment among library staff of public senior high schools (SMA Negeri) in Jambi Province, both directly and indirectly. The research employed a quantitative approach with a cluster sampling technique across three regions Jambi City, Tanjung Jabung Timur Regency, and Merangin Regencywith a total of 132 respondents, 97 of whom were included in the analytical sample. Data were processed using SmartPLS 3.0 through structural model testing (inner model) to examine causal relationships among variables.The results indicate that leadership style does not have a significant direct effect on work motivation, whereas organizational culture shows a strong and significant direct effect on the work motivation of library staff. Additionally, leadership style and organizational culture jointly have a significant impact on work motivation. Regarding organizational commitment, the findings reveal that leadership style, organizational culture, and work motivation each have a positive and significant direct effect. Further results show that both leadership style and organizational culture exert significant indirect effects on organizational commitment through work motivation, suggesting that work motivation functions as a mediating variable in these relationships. Overall, this study concludes that organizational culture is the most dominant factor influencing both work motivation and organizational commitment, while work motivation strengthens the relationship between leadership and cultural factors and the commitment of library staff. Therefore, efforts to enhance organizational commitment among library personnel in public senior high schools in Jambi Province should focus on cultivating a positive organizational culture, improving effective leadership practices, and providing continuous motivational support.